THE SIGNIFICANCE OF LEXICAL LEVEL IN STYLISTIC ANALYSIS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article provides a comprehensive exploration of the lexical level within stylistic analysis, emphasizing its pivotal role in decoding the nuances of literary works. It elucidates how the choice, arrangement, and usage of words contribute significantly to understanding an author's style, character development, setting depiction, and thematic concerns. The annotation further expands on specific elements of lexical analysis, such as connotations, word economy, semantic fields, shifts in register, intertextuality, and rhetorical devices. By highlighting these aspects, the annotation underscores the importance of delving into the intricacies of language at the lexical level to unearth the layers of meaning, literary craftsmanship, and artistic intentions woven into a text. This in-depth analysis encourages a nuanced interpretation, fostering a deeper appreciation and comprehension of the complexities inherent in written works.